The effects of different prior exercises on oxygen uptake kinetics and exercise tolerance in supramaximal running performance - Moilanen, E. (University of Jyväskylä, 2020)
Introduction. Rapid response of VO2 kinetics at the beginning of the endurance exercise has been found beneficial for the performance. In sports, prior exercises have been used to enhance the VO2 kinetics as well as the exercise tolerance of the performance, and many earlier studies have shown beneficial effects of prior high intensity exercises on these variables. In addition to the capacities of the respiratory and circulatory systems, the importance of neuromuscular capacities in endurance performance have been noticed. The aim of this study was to investigate the effects of continuous severe intensity prior exercise and intermittent prior exercise on VO2 kinetics and exercise tolerance in supramaximal running exercise compared to continuous moderate intensity prior exercise. The second aim was to investigate associations between neuromuscular abilities and endurance performance. Methods. Participants (n=10) visited the laboratory five times separated by 3-7 days. During the first visit, incremental VO2max test was completed by running on a treadmill. The next three visits included supramaximal running tests on a treadmill with three different prior exercises, in randomized order. Prior exercise protocols were continuous moderate intensity (control condition, S1), continuous severe intensity (S2) and intermittent (S3) prior exercise. The intensities were 75 % of LT for S1, 70 % ? for S2 and 110 % vVO2max for S3 and for the supramaximal test. The duration of the prior exercise protocols was 6 minutes. The recovery period between the prior exercise protocol and supramaximal test was 20 minutes including 15 minutes of passive and 5 minutes of active recovery. Supramaximal tests were done until volitional exhaustion. During the last visit, neuromuscular performance, including leg press 1 RM, CMJ and 30-m speed test, was measured. Results. Statistically significant difference (p < 0.05) was found between S1 and S2 in total VO2 measured in 15-120 s of the supramaximal performance (mean ± SD 5867 ± 1506 for S1 and 5963 ± 1496 for S2), but there were no significant differences between conditions concerning any other variables of VO2 kinetics. There were no statistically significant differences between the conditions in exercise tolerance. Significant correlations were found between vVO2max and leg press 1 RM (r = 0.688, p < 0.05) and vVO2max and speed test 0-10 m time (r = -0.692, p < 0.05) and time to exhaustion of the supramaximal test S1 and CMJ (r = 0.661, p < 0.05), supramaximal test S2 and CMJ (r = 0.833, p < 0.01) and supramaximal test S3 and CMJ (r = 0.809, p < 0.01). Conclusion. Continuous severe intensity prior exercise can increase energy production from aerobic sources during the first two minutes of the following supramaximal performance when compared to moderate intensity prior exercise, but this might not improve the performance in exercise with supramaximal intensity and short duration. Prior exercise intensity and recovery time should be chosen so that it improves performance but does not produce too much fatigue. Also, the individual differences should be considered. Neuromuscular performance was found to correlate with the endurance performance, which supports the importance of neuromuscular ability also in endurance sports.